Impacts of introducing a convective gravity‐wave parameterization upon the QBO in the Met Office Unified Model. Issue 9 (14th May 2013) - Kim, Y.‐H.; Bushell, A. C.; Jackson, D. R.; Chun, H.‐Y.
<x xml:space="preserve">Abstract</x> [1] A convective gravity‐wave parameterization (GWP) is introduced in the Met Office Unified Model (MetUM) in addition to the existing GWPs, and the tropical quasi‐biennial oscillation (QBO) is simulated. We replace a significant amount of momentum flux, which is originally launched by the background GWP, with the convective gravity‐wave (CGW) momentum flux with a broad wave spectrum that is explicitly determined by the convective sources. Compared to the experiment without the CGW parameterization, including the CGW parameterization results in a greater variability in the duration of each phase of the QBO, which is closer to observed. Including the CGWs also strengthens the annual cycle of zonal wind and it allows for stronger modulation of the semi‐annual oscillation.